I wonder why Zips have teeth : and other questions about inventions - Taylor, Barbara (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why Zips Have Teeth is jam-packed with fascinating facts about inventions, from 'When did home computer games appear?' to 'What did people use before fridges?'
Includes index
Keywords: History